THE ROLE OF ORGANIZATIONAL CULTURE, MOTIVATION, AND TRAINING, IN ORDER TO INCREASE EMPLOYEE PERFORMANCE AT THE BAPPEDA (REGIONAL DEVELOPMENT PLANNING BOARD) OF WEST JAVA PROVINCE - Tanto Sriyono Suhodo; Deden Komar Priatna; Tunggul Harymurtie (Dinasti International Journal of Education Management And Social Science, 2020)
The performance of members of an organization is needed to support organizational performance. The performance of employees at the BAPPEDA (Regional Development Planning Board) of West Java Province will affect the performance of this government agency. The purpose of this study was to find out how much the role of organizational culture, motivation, and training in order to improve the performance of employees in the Regional Development Planning Board of West Java Province, both simultaneously and partially. The method used in this study is descriptive and verification method. The source of data in this study were employees of the Regional Development Planning Board of West Java Province. Primary data was collected by using questionnaires and interviews with Regional Development Planning Board of West Java Province employees. Secondary data is collected by tracing documents that are relevant to the problem under study. The results of descriptive data analysis on research variables, showed that organizational culture, motivation, training, and employee performance at the Regional Development Planning Board of West Java Province were in the good category. Organizational culture, motivation, and training have a significant role in order to improve employee performance, which is equal to 72.2%. Motivational variables have a more dominant role in order to improve the performance of employees of the Regional Development Planning Board of West Java Province because they have the highest beta value, 37.1%.